The Use of Testing, Demonstrating, Practicing, and Revising (TDPR) Technique to Improve Students' Ability in Pronouncing Plosive Consonants - Rima Rahmaniah (Linguistics and ELT Journal, 2017)
Testing, Demonstrating, Practicing and Revising (TDPR) technique is a technique which includes testing, demonstrating, practicing and revising activities to know and improve the students’ pronunciation ability. Deriving from the importance of pronunciation, the main purpose of the current study is to investigate the use of Testing, Demonstrating, Practicing and Revising (TDPR) technique to improve the students’ ability in pronouncing plosive consonants. Based on the purpose of the study, a series of classroom activities with TDPR technique was done. In gathering the data, the researcher applied a quasi-experimental research method. Pre-test and post-test were distributed to 72 students of SMKN 1 Praya Tengah. The result of the study has revealed that there was a significant difference between the mean of pre-test and the post-test, t-test 5.10 ˃ t-table 1.994, it means that the null hypothesis (Ho) is rejected meanwhile alternative hypothesis (Ha) is accepted. It proved that the TDPR technique can improve students’ ability in pronouncing plosive consonants.